2012
DOI: 10.1007/s00359-012-0721-6
|View full text |Cite
|
Sign up to set email alerts
|

Adult neurogenesis in the brain of the Mozambique tilapia, Oreochromis mossambicus

Abstract: Although the generation of new neurons in the adult nervous system ('adult neurogenesis') has been studied intensively in recent years, little is known about this phenomenon in non-mammalian vertebrates. Here, we examined the generation, migration, and differentiation of new neurons and glial cells in the Mozambique tilapia (Oreochromis mossambicus), a representative of one of the largest vertebrate taxonomic orders, the perciform fish. The vast majority of new cells in the brain are born in specific prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 74 publications
8
32
0
Order By: Relevance
“…This is in agreement with the results reported in A. leptorhynchus, O. latipes, N. Furzeri, A. burtoni , and O. mossambicus , (Zupanc and Horschke, 1995; Kuroyanagi et al, 2010; Terzibasi et al, 2012; Maruska et al, 2012; Teles et al, 2012) and D. rerio (Zupanc et al, 2005; Zupanc, 2011). However, according to Adolf et al (2006) and Grandel et al (2006) this proliferation zone in D. rerio is restricted to the ventral portion of the diencephalic ventricle.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is in agreement with the results reported in A. leptorhynchus, O. latipes, N. Furzeri, A. burtoni , and O. mossambicus , (Zupanc and Horschke, 1995; Kuroyanagi et al, 2010; Terzibasi et al, 2012; Maruska et al, 2012; Teles et al, 2012) and D. rerio (Zupanc et al, 2005; Zupanc, 2011). However, according to Adolf et al (2006) and Grandel et al (2006) this proliferation zone in D. rerio is restricted to the ventral portion of the diencephalic ventricle.…”
Section: Discussionsupporting
confidence: 91%
“…Very scarce proliferating cells were found in the OB of adult G. omarorum , most of which were located within the glomerular layer or at the dorsal-medial surface of the intermediate zone of the OB (corresponding to the rostralmost region of the telencephalic ventricle). This is consistent with the results reported in D. rerio (Byrd and Brunjes, 2001; Adolf et al, 2006; Grandel et al, 2006; Zupanc, 2011), A. burtoni (Maruska et al, 2012), and O. mossambicus (Teles et al, 2012). Conversely, Ekström et al (2001) reported proliferating cells at the internal cell layer of G. aculeatus , and Fernández et al (2011) found labeled cells in all OB laminae of Austrolebias (with the highest long term thymidine label retaining cells concentration in its medial and rostral part.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Currently, it is known that in mammals, adult neurogenesis takes place only in a few areas (Eriksson et al, 1998;Gould et al, 1999;Peretto et al, 1999;Lee and Blackshaw, 2012) while numerous studies have reported widespread neurogenesis in non-mammals such as fish (Zikopoulos et al, 2001;Zupanc et al, 2005;Grandel et al, 2006;Ampatzis and Dermon, 2007;Teles et al, 2012), amphibians (Richter and Kranz, 1981;Simmons et al, 2008;D'Amico et al, 2013), reptiles (Lo´pez-Garcı´a et al, 1988, 1990DelgadoGonza´lez et al, 2011) and birds (Scharff et al, 2000). In this context, very recent studies have described a new germinative zone in the adult mammalian brain, located in the hypothalamic region (Kokoeva et al, 2005;Lee and Blackshaw, 2012;Cheng, 2013), in agreement with what was found in amphibians (Simmons et al, 2008).…”
Section: Xulk4 Expression Patterns In the Forebrainmentioning
confidence: 99%